The Womens Sports Foundation
Homepage of the English Womens Sports Foundation. The Womens Sports Foundation (founded in 1984) is the only organisation in the UK that is solely committed to improving and promoting opportunities for women and girls in sport at every level. The vision is: 'To pursue and promote equity for women in and through sport' The WSF ha five key aims: Increase awareness about the issues surrounding women and girls involvement in sport. Support women and girls to become involved in sport at all levels and in all capacities. Encourage organisations to improve access to sporting opportunities for women and girls. Challenge instances of inequality in sport and seek to bring about change. Raise the visibility of all British Sportswomen. With the WSF Young Elite Sportswomen Seminars the WSF gives female athletes the right support and advice on how to get to the top. The Womens Sports Foundation produces a quarterly members newsletter full of articles relating to women and girls' sport.